Dynamic analysis of interfacial crack problems in anisotropic bi-materials by a time-domain BEM - Lei, J.; Garcia-Sanchez, F.; Wünsche, M.; Zhang, C.; Wang, Y.; Saez, A.
A time-domain boundary element method (BEM)together with the sub-domain technique is applied to study dynamic interfacial crack problems in two-dimensional (2D), piecewise homogeneous, anisotropic and linear elastic bi-materials. The bi-material system is divided into two homogeneous sub-domains along the interface and the traditional displacement boundary integral equations (BIEs)are applied on the boundary of each sub-domain. The present time-domain BEM uses a quadrature formula for the temporal discretization to approximate the convolution integrals and a collocation method for the spatial discretization. Quadratic quarter-point elements are implemented at the tips of the interface cracks. A displacement extrapolation technique is used to determine the complex dynamic stress intensity factors (SIFs). Numerical examples for computing the complex dynamic SIFs are presented and discussed to demonstrate the accuracy and the efficiency of the present time-domain BEM.
Keywords: DYNAMIC FRACTURE MECHANICS; DYNAMIC STRESS INTENSITY FACTORS; ANISOTROPIC BI-MATERIALS; INTERFACE CRACKS; TIME-DOMAIN BOUNDARY ELEMENT METHOD